Microplastic sampling with the AVANI trawl compared to two neuston trawls in the Bay of Bengal and South Pacific. (January 2018) - Eriksen, Marcus; Liboiron, Max; Kiessling, Tim; Charron, Louis; Alling, Abigail; Lebreton, Laurent; Richards, Heather; Roth, Barent; Ory, Nicolas C.; Hidalgo-Ruz, Valeria; Meerhoff, Erika; Box, Carolynn; et al.
Abstract: Many typical neuston trawls can only be used during relatively calm sea states and slow tow speeds. During two expeditions to the Bay of Bengal and the eastern South Pacific we investigated whether the new, high-speed AVANI trawl (All-purpose Velocity Accelerated Net Instrument) collects similar amounts and types of microplastics as two established scientific trawl designs, the manta trawl and the DiSalvo neuston net. Using a 335 μm net, the AVANI trawl can collect microplastics from the sea surface at speeds up to 8 knots as it "skis" across the surface, whereas the manta and DiSalvo neuston trawls must be towed slowly in a less turbulent sea state and often represent shorter tow lengths. Generally, the AVANI trawl collected a greater numerical abundance and weight of plastic particles in most size classes and debris types than the manta trawl and DiSalvo neuston net, likely because these trawls only skim the surface layer while the AVANI trawl, moving vertically in a random fashion, collects a "deeper" sample, capturing the few plastics that float slightly lower in the water column. However, the samples did not differ enough that results were significantly affected, suggesting that studies done with these different trawls are comparable. The advantage of the AVANI trawl over traditional research trawls is that it allows for collection on vessels underway at high speeds and during long transits, allowing for a nearly continuous sampling effort over long distances. As local surface currents make sea surface abundance widely heterogeneous, widely spaced short-tow trawls, such as the manta and DiSalvo trawls, can catch or miss hotspots or meso-scale variability of microplastic accumulations, whereas the AVANI trawl, if utilized for back-to-back tows of intermediate distances (5–10 km), can bridge variable wind conditions and debris concentrations potentially reducing variance and provide a greater resolution of spatial distribution. Graphical abstract: Highlights: The new AVANI high-speed neuston trawl is comparable to standard scientific trawls. Paired AVANI and neuston trawl samples had similar microplastic abundances. The AVANI trawl provides high-speed continuous sampling to cover long transects. Weather and currents likely account for greater variability than trawl type. Abstract : The AVANI trawl is a valid neuston trawl, comparable to standard scientific trawls to study floating microplastics. It is unique in that it provides high-speed continuous sampling to cover long transects.